Efforts to Increase Self-Confidence in Early Childhood Through Islamic Singing Activities - Hoktaviandri, Hoktaviandri; Arifin, Zainul; Putri, Yuliani Eka; Yusneli, Yusneli (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2025)
Self-confidence is a crucial aspect of early childhood development because it forms the basis for children's courage to perform, express their ideas, and actively participate in learning activities and social life. Children with self-confidence tend to be more optimistic, independent in decision-making, and motivated to achieve. Conversely, low self-confidence can hinder a child's socialization process and potential development. This study aims to describe how Islamic singing activities can be used as a learning strategy to increase self-confidence while instilling the values of monotheism in early childhood. The research method used was qualitative with a descriptive approach. The subjects were early childhood students at SPS IT Ar Rahim, with data sources obtained from teachers and the principal selected through purposive sampling based on specific criteria. Data were collected through direct observation, in-depth interviews, and documentation of learning activities. The primary research instrument was the researcher herself, assisted by interview guidelines, observation sheets, and field notes. Data analysis was conducted thematically using the Miles & Huberman model, encompassing the stages of data reduction, data presentation, and conclusion drawing. Data validity was maintained using source and method triangulation techniques.